Do Women have a Choice to Construct their World - Kaya, Anıl Kemal (Online Journal of Communication and Media Technologies, 2011)
In view of the fact that, the world is not stabile and most of the things change very rapidly. In spite of this, women’s place and rights in some fields seem still the same. This paper seeks to explore whether women have any choice to construct their world in their life. This research focuses on analyzing the political economy and the cultural studies perspective to find out some answers for the research questions. Also Berger, Douglas, Foucault and Habermas perspectives have been analyzed to understand better if women have a choice to construct their world. The result points out that, the world can change but to make some changes, awareness of the problem is important. The importance of this paper is to make society aware of inequality rights among genders.
Keywords: Women - Labor Force - Political Rights; Women’s Rights and Gender Equality